Notes in the graph theory. A manuscript (with flower snark J5) - Grinbergs, Emanuels (My University, 2013)
This fragment of manuscripts, written in Latvian, is taken from a hardcover notebook of E.Grinbergs. The date when these notes started 29.7.72 is clearly seen on the first page, on the page 7 the date is 31.8.72, on 10th - 28.8.73. On page 6, rights, a graph corresponding to flower snark J5 can be clearly seen, see http://en.wikipedia.org/wiki/Flower_snark. This sample of manuscript shows that E. Grinbergs was building these graphs before 1975, when graphs named flower snarks were introduced by Rufus Isaacs.
Keywords: combinatorics, graph theory, flower snarks